Effect of vitamin D3 supplementation on thyroid function of clinically healthy dogs - Hashemi, S.; Shomali, T.; Derakhshandeh, N.; Nazifi, S. (Frontiers in Veterinary Science, 2025)
IntroductionVitamin D has diverse effects on different organ functions. This study evaluated the effect of vitamin D3 supplementation on thyroid function of healthy dogs by repeated assays of thyroid hormones (including total and free T4 and T3) as well as TSH levels during a 6 week-period.MethodsEight healthy adult male dogs received vitamin D3 supplements at the dose of 50 IU/kg BW per day. Venous blood samples were collected on days 0, 14, 28 and 42 of the experiment.ResultsSix-week vitamin D3 supplementation statistically increased serum T4 levels [F (1.89, 13.2) =8.39 and p = 0.004]. Serum T4 levels on days 28 and 42 were significantly higher than the baseline (day 0) (p < 0.05). There was also a statistically significant effect of duration of supplementation on serum fT4 levels, [F (1.63, 11.4) = 12.53, p = 0.014], although the difference was only significant between days 0 and 42. Changes in serum levels of T3 and fT3 were non-significant. TSH levels showed a significant decrease during the whole time of the study [F (1.17, 7.02) = 26.4 and p = 0.001]. On days 14, 28 and 42 this parameter was statistically lower than day 0. Changes in serum T3/T4 during time were not statistically significant. However; the fT3/fT4 ratio showed a downward change during study [F (1.77, 8.87) = 5.18 and p = 0.035]. The fT3/fT4 ratio on day 42 of the experiment was significantly lower than day 0.DiscussionVitamin D3 supplementation to healthy dogs is associated with a time-dependent change in thyroid hormone profile (increased serum T4 and fT4) which are probably mediated at the thyroid gland level as shown by the negative feedback on serum TSH concentrations. These findings pave the road for future studies on the plausible effects of this vitamin on thyroid function of hypothyroid dogs.